Reseña de Juan Linz y Alfred Stepan, Problems of Democratic Transition and Consolidation: Southern Europe, South America and Post-communist Europe - Sarquís, David (Revista Mexicana de Política Exterior, 2022)
Juan Linz y Alfred Stepan, Problems of Democratic Transition and Consolidation: Southern Europe, South America and Post-communist Europe, Baltimore, Johns Hopkins University Press, 1996, 479 pp.